Multicentennial Variability of the Sea Surface Temperature Gradient across the Subpolar North Atlantic over the Last 2.8 kyr - Miettinen, A.; Divine, D.V.; Koc, N.; Godtliebsen, F.; Hall, I.R. (Journal of Climate, 2012)
A 2800-yr-long August sea surface temperature (aSST) record based on fossil diatom assemblages is generated from a marine sediment core from the northern subpolar North Atlantic. The record is compared with the aSST record from the Norwegian Sea to explore the variability of the aSST gradient between these areas during the late Holocene. The aSST records demonstrate the opposite climate tendencies toward a persistent warming in the core site in the subpolar North Atlantic and cooling in the Norwegian Sea. At the multicentennial scale of aSST variability of 600–900 yr, the records are nearly in antiphase with warmer (colder) periods in the subpolar North Atlantic corresponding to the colder (warmer) periods in the Norwegian Sea. At the shorter time scale of 200–450 yr, the records display a phase-locked behavior with a tendency for the positive aSST anomalies in the Norwegian Sea to lead, by ~30 yr, the negative aSST anomalies in the subpolar North Atlantic. This apparent aSST seesaw might have an effect on two major anomalies of the European climate of the past Millennium: Medieval Warm Period (MWP) and the Little Ice Age (LIA). During the MWP warming of the sea surface in the Norwegian Sea occurred in parallel with cooling in the northern subpolar North Atlantic, whereas the opposite pattern emerged during the LIA. The results suggest that the observed aSST seesaw between the subpolar North Atlantic and the Norwegian Sea could be a surface expression of the variability of the eastern and western branches of the Atlantic meridional overturning circulation (AMOC) with a possible amplification through atmospheric feedback.